Development of a microthrust balance and ion beam measurement system: Characterizing a dual-mode thruster for spacecraft. (June 2019) - Little, Bryan; Jugroot, Manish
Abstract: There is a rapid progression toward spacecraft miniaturization due to the prospect of reduced launch costs, the requirement for satellite constellations, and the integration of microelectromechanical systems (MEMS). Satellite propulsion is required for increased mission flexibility and orbital debris mitigation, but down-scaling of such devices has proven non-trivial. Some electrostatic thrusters are both challenging and promising given their increase in performance with small geometry, but the relatively low thrust produced through ion acceleration limits their mission applicability. For this reason, it may be desirable to produce thrusters that are able operate across a wide range of specific impulses, depending on maneuver time, thrust bit requirements, and several other factors that influence propulsion system selection. At RAPPEL, a bimodal thruster that can operate at high specific impulse with electrospray propulsion or high thrust using cold gas expansion has been developed. Inevitably, such a propulsion system comes with complications related to performance characterization. A novel and economical data acquisition system has been established to measure the performance of both modes in high vacuum. For the cold gas mode, a torsional thrust balance was built in-house to measure thrust levels between 1 − 15 m N, and can be easily modified for lower ranges. The natural frequency of the thrust stand was measured to be 5.6 H z . The vacuum system sustained pressures below 5 m b a r while the cold gas nozzle operated, and 1.3 × 10 − 5 m b a r during electrospray operation. A 3-D printed linear cold gas nozzle was used to validate the thrust stand. Its thrust was close to 9 m N at a mass flow rate of 20 m g / s of nitrogen, producing a specific impulse of just under 45 s . Due to the noise present in thrust stand measurements at the sub- m N force-level produced by electrosprays, the thrust stand was built to also accommodate a complementary ion beam current measurement system. The power processing unit, used to generate square-wave ± 2500 V signals using optodiodes, was built to operate a bipolar ionic liquid ion source (ILIS). The rise and fall times of the push/pull switch were close to 1 m s and 30 m s, respectively. The electrical power system used to operate the electrospray and measure its performance is examined in detail, followed by the results from validation of both data acquisition systems. Highlights: Insights into advantages of a bimodal electric micro‐propulsion system. Exploring a miniaturized electrospray coupled to a cold gas thruster. Performance of a bipolar operation electrospray. Design of a thrust balance and complementary data acquisition system to measure current flow.